A Triple Layer of Immiscible Solvents for NMR Sample Preparation: Enhanced Sensitivity and Reduced Deuterated Solvent. Issue 44 (27th November 2019) - Baishya, Bikash; Chandra, Atish
Abstract: NMR spectroscopy is often constrained by lack of sensitivity. A contributing factor towards this reduced sensitivity stems from NMR sample preparation‐ the sample dilution. Organic chemists routinely prepare NMR sample by filling the lowermost 4 cm length of a regular 5 mm 0.d. tube that holds approximately 0.55 ml of a deuterated solvent. This is equivalent to diluting the sample as the signal mainly comes from the central part of length 1.8 cm corresponding to typical coil length of 1.8 cm. The top and bottom part of the sample contributes less signal as they are far from the coil but are crucial for maintaining magnetic field homogeneity. Consequently, the requirement of the expensive deuterated solvent increases. Herein, we explore a way of sample preparation which involves sandwiching a small amount of the deuterated solvent containing the analyte between two non‐deuterated solvents, which are immiscible with the former using a regular 5 mm o.d. tube. The total length is still 4 cm. The analyte now being closer to NMR coil, improves sensitivity and reduces deuterated solvent hitherto required by a factor of two‐fold. 13 C and 15 N spectra display more than a two‐fold higher signal to noise ratio. 1 H, 19 F, and 31 P spectra also displayed enhanced sensitivity. Examples of various solvent systems designed are detailed here. Two‐dimensional NMR is also provided. Abstract : NMR sample preparation using triple layer of immiscible solvents is presented, where the analyte in a small amount of deuterated solvent is sandwiched between two non‐deuterated solvents, using a regular 5 mm o.d. tube. This solvent encoded method enhances sensitivity of NMR signals and reduces requirement of deuterated solvents.